The Personality Assessment Screener as a Predictor of Self-Injuring Thoughts and Behavior Crisis Events in a Male Prison Sample - Truong, Tiffany N. (Criminal justice and behavior, 2022)
Mental disorder is widespread in correctional settings, as is the potential for suicide and self-harm among detained individuals. The ability of the Personality Assessment Screener (PAS) to identify potential mental health problems has been the focus of recent research in corrections, but few studies have examined the prediction of crisis events related to self-injuring thoughts and behaviors. We explored the utility of repeated PAS administrations among men incarcerated in prison (N = 270) to identify those at risk for a subsequent crisis event involving potential self-harm. Baseline PAS total scores predicted the odds of experiencing a crisis event (odds ratio = 3.76–4.46) and, importantly, changes in PAS total scores over time incrementally predicted such events beyond scores assessed at a single time-point, t(49) = –2.14, p = .037. These preliminary findings demonstrate promise for the PAS as an indicator of potential self-injuring crisis events when administered at intake and regular intervals throughout incarceration.